The Achievements of the Rochester School in the Field of Critical Art History - Mitic, Lora (Actual Problems of Theory and History of Art, 2025)
This work is dealing with the problem of changing methodological structure of the art history as a discipline during the last three decades and placing the activity of the Rochester School on the map of these changes. Its most important characteristic is contextual approach to art.
Keywords: critical art history; Rochester School; critical approach; methodological structure; context